The potential of carbonate ramps to record C-isotope shifts: insights from the upper Miocene of the Central Mediterranean area - Cornacchia, Irene; Munnecke, Axel; Brandano, Marco (Lethaia, 2020)
The late Miocene is a crucial interval for global climate evolution as well as for the regional geodynamic evolution of the Central Mediterranean area. It spans the transition from the warm Mid Miocene Climatic Optimum, associated with the major Monterey Carbon Isotope Excursion, to the cooler Pliocene, characterized by a bipolar glaciation. Within this climatic transition, during the early Tortonian, a positive carbon isotope excursion related to a global carbon cycle perturbation is recorded, named Carbon Maximum 7 (CM7). In this study, two upper Serravallian–lower Tortonian carbonate ramps of the Central Mediterranean have been analysed: the Latium-Abruzzi and the Apula ramps (Central Apennines, Central Italy). Carbon isotope ratios have been coupled with facies and microfacies analyses with the aims: (1) to identify the CM7 in the Central Mediterranean carbonate ramp successions; (2) to evaluate potential carbonate factory changes or demises related to the CM7; and (3) to discriminate the role of global vs regional factors in affecting the Mediterranean carbonate ramps. The two studied ramps show different evolutions due to regional geodynamics causes. The Latium-Abruzzi ramp drowns in the Tortonian, while the Apula shows a regressive trend, with upper Tortonian middle ramp facies overlying the lower Tortonian outer ramp. Despite the complex geodynamic setting, a positive carbon isotope shift has been identified in both ramps and correlated with the CM7. This positive carbon isotope shift may be linked to the strengthening of the global ocean circulation during the late Miocene cooling. This strengthening of the circulation enhanced the coastal upwelling, bringing nutrient-rich waters to the surface and triggering an enhanced primary productivity consistent with the CM7.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Apennines; C-isotopes; carbonate ramps; late Miocene; Mediterranean